The model development of industrial brand loyalty: Assessing the rational and emotional aspects as antecedents of loyalty - Andreas Samudro; Vonny Susanti (Cogent Business & Management, 2021)
The purpose of the study is to develop a brand loyalty model with perspectives from rational and emotional aspects. The research investigates the relevant antecedents of the brand loyalty model with the respondents from various industries in the chemical emulsion market. The research is a quantitative approach with SEM-PLS employed to run the data, whereas the data is conducted and collected from the field survey. The study demonstrates the robustness of the model with direct relationships between the constructs in the model. Moreover, it confirms that rational brand quality influences brand loyalty stronger than emotional brand associations; further perceived value has the weakest influence on satisfaction. Authors encourage replicated research with a broader range of product categories to validate the results. The ideal model should be able to be implemented with generalization. The research has an insight into the two-sided role of rational and emotional elements during the decision process and their role in satisfaction and brand loyalty; moreover, the proposed model also adds perceived value. With the investigation of the direct and indirect effects among the constructs of the model, this model is considered new in industrial branding; therefore, the paper fulfills the research gap and contributes novelty.
Keywords: 650; Rational brand quality; emotional brand associations; perceived value; customer satisfaction; brand loyalty